In vitro free radical formation following exposure to Technetium-99M (99mTc) / Ahmad Akmal Mohamad Bee - Mohamad Bee, Ahmad Akmal (2012)
This study is about the formation of free radical following exposure to technetium-99m (99mTc). The objectives are to assess the presence of free radical following administration of 99mTc-HMPAO and also to assess the optimum time and activity to induce the free radical formation. This 99mTc will irradiate and produce the free radical known as auger electrons.